The improvement in magazine illustration in the last twenty-five years - Newell, Clara Verena (My University, 1896)
Introduction: Our world today is full of pictures. Every paper, magazine and book which seeks to be truly instructive and entertaining, uses them freely. If such a thing is possible for us who have been accustomed all our lives to having “fact and fancy” impressed upon us by the double means of picture and style, let us stop and think what our loss would be if deprived of these, our dear, familiar friends. Then will the power of a good illustration be more forcibly impressed upon us.
Citation: Newell, Clara Verena. The improvement in magazine illustration in the last twenty-five years. Senior thesis, Kansas State Agricultural College, 1896.
Morse Department of Special Collections
Keywords: Magazine; Entertainment; Illustration; Theses; Manuscripts (documents)